Faktor-faktor yang mempengaruhi pengangguran terbuka di Provinsi Jambi - Anzas Fernando Sirait; Yulmardi Yulmardi; Adi Bhakti (Konsentrasi Pembangunan Regional dan Publik, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2018)
This study aims to analyze: 1) the development of open unemployment, investment, wages, economic growth and inflation in Jambi Province; (2) the effect of investment, wages, economic growth and inflation on open unemployment in Jambi Province. The data used are secondary data for the period 2000 - 2016 sourced from BPS Jambi Province. Data were analyzed descriptively as well as multiple regression models. The results of the study found: 1) The average level of open unemployment in Jambi Province during 2000-2016 was 5.44 percent per year. On the other hand, in the same period, domestic investment grew by an average of 1.16 percent per year, wages grew on average by 1.54 percent per year, economic growth averaged 6.45 percent per year, inflation averaged by 8.96 percent per year, and investment grew by an average of 11.64 percent per year; 2) Simultaneously, wages, economic growth, inflation and investment have a significant effect on open unemployment. Partially wages have a positive and significant effect, economic growth has a negative and significant effect, inflation has no significant effect and investment has a negative and significant effect on open unemployment.